Trillion game. Volume 7 - Inagaki, Riichiro (VIZ Media, LLC, 2025)
"Self-proclaimed "world's greediest man" Haru and timid computer whiz Gaku set out to make a trillion dollars. They start the company Trillion Game to accomplish this task and hope to iron out the details as they go. With charm, technical skills, and no business plan, can these unlikely friends reach their lofty goal?Haru and Gaku team up with the news department of Kawara TV to launch Trillion TV. Haru claims that news is the real "money tree" and goes all-in on streaming news. But what is he really after...?"-- Back cover.